Against Aesthetic/Sensory Dependence - Benovsky, Jiri (The Nordic Journal of Aesthetics, 2017)
In his book The Metaphysics of Beauty (2001) Nick Zangwill argues for the claim that aesthetic properties metaphysically necessarily depend on sensory properties. This claim plays a role in his argument against physicalist aesthetic realism as well as in the formulation of his own response- dependence view. In this article, I offer reasons to resist the aesthetic/ sensory dependence claim by a discussion of the case of theories, theorems, proofs, and similar theoretical objects, which do possess genuinely aesthetic properties, while these do not depend on any sensory properties. I argue against Zangwill’s claim that such attributions of aesthetic properties are merely metaphorical.